(untitled) (Comparative Professional Pedagogy, 2024)
The article presents the results of the analysis of the problem of dual education implementation in higher education of Israel. It is that in recent years there have been taking place growing trends towards expanding the areas in which dual learning is used, including multi-level systems of continuing teacher education. Israeli higher education institutions create conditions for different models of teacher training: basic, additional, parallel and individual. The study found that there are specific factors that significantly affect the understanding of the dual form of education in the context of Israeli realities. In Israel, dual education is considered as one of the key models of vocational education, which includes cooperation with enterprises, a combination of theoretical and practical training, and preparation of students for the real requirements of the labor market. In Israel, there are programs specifically designed for adults that facilitate obtaining professional certificates issued by the Ministry of Social Policy. Government programs aimed at increasing the employment rate among retrained professionals are also important (career counseling centers, seminars on employment technologies, joint research with employers to identify relevant professions and qualifications, and support for providers of relevant educational services). A set of methods of theoretical research into the state of dual education implementation in the system of higher pedagogical education in Israel contribute to the identification of the main trends of its development in the 21st century, in particular, compliance with the standards of education quality assurance. It is concluded that a significant achievement of the Israeli education system is the models that ensure productive employment of future specialists and the relevance of their qualifications to the requirements of the labor market. In general, it can be stated that the practical experience of Israel in implementing dual education in the system of teacher education can be used in Ukraine to achieve the strategic goals of ensuring the quality of future teachers’ training.